Low-temperature-processed ZnO thin films as electron transporting layer to achieve stable perovskite solar cells - Chalita Horachit (2018)
© 2018, Springer Science+Business Media, LLC, part of Springer Nature. Morphology and surface property of ZnO thin films as electron transporting layer in perovskite solar cells are crucial for obtaining high-efficient and stable perovskite solar cells. In this work, two different preparation methods of ZnO thin films were carried out and the photovoltaic performances of the subsequent perovskite solar cells were investigated. ZnO thin film prepared by sol–gel method was homogenous but provided high series resistance in solar cells, leading to low short circuit current density. Lower series resistance of solar cell was obtained from homogeneous ZnO thin film from spin-coating of colloidal ZnO nanoparticles (synthesized by hydrolysis–condensation) in a mixture of 1-butanol, chloroform and methanol. The perovskite solar cells using this film achieved the highest power conversion efficiency (PCE) of 4.79% when poly(3-hexylthiophene) was used as a hole transporting layer. In addition, the stability of perovskite solar cells was also examined by measuring the photovoltaic characteristic for six consecutive weeks with the interval of 2 weeks. It was found that using double layers of the sol–gel ZnO and ZnO nanoparticles provided better stability with no degradation of PCE in 10 weeks. Therefore, this work provides a simple method for preparing homogeneous ZnO thin films in order to achieve stable perovskite solar cells, also for controlling their surface properties which help better understand the characteristics of perovskite solar cells.